PENGARUH ADIKSI SMARTPHONE TERHADAP PROKRASTINASI AKADEMIK MELALUI MANAJEMEN WAKTU PADA MAHASISWA PENDIDIKAN AKUNTANSI - Dian Pramita Sari; Asri Diah Susanti (Jurnal Pengembangan Pendidikan Akuntansi dan Keuangan (JPPAK), 2026)
ABSTRACTThis study analyzes how smartphone addiction influences academic procrastination through time management among accounting education students. A quantitative causal approach was used. The study population consisted of accounting education students. Simple random sampling was used to select 184 students. Data were collected through an online questionnaire on Google Forms. Validity was tested using the Pearson product-moment correlation method, and prerequisite analyses included normality, linearity, multicollinearity, and heteroscedasticity tests. Path analysis, the coefficient of determination (R²), and the Sobel test were used to identify indirect effects. The findings are as follows: First, smartphone addiction has a significant direct effect on academic procrastination. Second, smartphone addiction has a significant direct effect on time management. Third, time management has a significant direct effect on academic procrastination. Fourth, smartphone addiction has a significant indirect effect on academic procrastination through time management as a mediating variableKeywords: Academic Procrastination; Smartphone Addiction; Time Management.